2006
DOI: 10.1161/circulationaha.105.609883
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Mitral Annuloplasty

Abstract: Background-To allow performance of "stand-alone" mitral annuloplasty with minimal invasiveness, percutaneous techniques consisting of delivery into the coronary sinus (CS) of devices intended to shrink the mitral valve annulus have recently been tested in animal models. These techniques exploit the anatomic proximity of the CS and mitral valve annulus in ovine or dogs. Knowledge of a detailed anatomic relationship between the CS, coronary arteries, and mitral valve annulus in humans is essential to define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(41 citation statements)
references
References 18 publications
(13 reference statements)
0
41
0
Order By: Relevance
“…In 2006 Maselli et al [11] published the results of an anatomical study of the human CS in relation to the MV and coronary arteries in 61 excised cadaveric human hearts. They found that the LCx lies between the CS and the MV annulus in 63.9% -in our study it was 74.6%.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006 Maselli et al [11] published the results of an anatomical study of the human CS in relation to the MV and coronary arteries in 61 excised cadaveric human hearts. They found that the LCx lies between the CS and the MV annulus in 63.9% -in our study it was 74.6%.…”
Section: Discussionmentioning
confidence: 99%
“…For example Maselli et al [17], examined the hearts of 61 patients who had died of non-cardiological causes.…”
Section: Discussionmentioning
confidence: 99%
“…In an anatomical study of normal cadaveric hearts, Maselli et al reported that the coronary sinus was not in proximity of the mitral annulus in most humans, but was vertically away from it, running along the left atrial surface. 63- 65 In a more recent study, Plass et al also reported high variability in the angle between the coronary sinus and the mitral annulus, with a significant proportion of patients presenting with an oblique orientation of the sinus. 66 This oblique orientation of the coronary sinus not only reduces the ability of the inserted device to induce reduction in the septal lateral dimension of the mitral annulus, but also causes compression of the circumflex artery.…”
Section: Transcatheter Mitral Annuloplasty Coronary Sinus Devicesmentioning
confidence: 97%
“…66 This oblique orientation of the coronary sinus not only reduces the ability of the inserted device to induce reduction in the septal lateral dimension of the mitral annulus, but also causes compression of the circumflex artery. 65 Additionally, the mitral annulus is a dynamic structure with a sphincteric motion involving complex translational and rotational components, and interaction of the mitral annulus with the coronary sinus through the cardiac cycle might govern the efficiency of these devices that are designed for a more static environment. These anatomical constraints will not only induce high variability in patient outcomes using the same device, but might also fail in a variety of ways due to complexity in the mechanical loading in each patient, complicating the design specifications and safety testing protocols for such devices.…”
Section: Transcatheter Mitral Annuloplasty Coronary Sinus Devicesmentioning
confidence: 99%